Accessibility, priming, and political judgment. (December 2016) - Ottati, Victor; Wilson, Chase; Lambert, Alan
Highlights: Chronic accessibility plays an important role in political cognition. Recent research documents the effect of situational primes on political judgment. Affective primes elicit a variety of effects on political judgment. Media framing (including metaphoric framing) is a specific form of priming. Priming effects occur at encoding and at the time a political judgment is reported. Abstract : Classic and contemporary approaches to understanding political judgment implicitly acknowledged the role of chronic accessibility. Contemporary models also emphasize that situationally primed knowledge structures influence citizens' political attitudes and opinions. Priming effects are evident when specific concepts are primed (e.g., an issue, the American Flag, terrorism), and when media frames activate narratives that prime specific aspects of a political event. Metaphoric media frames (e.g., the presidential campaign is a horserace) can prime or highlight specific aspects of a political event (e.g., candidate electability) and thereby influence the public's attitudes and opinion (e.g., attitudes toward a political candidate). The immediate context in which political judgments are reported also produces priming effects on political judgment.